2015
DOI: 10.1515/amm-2015-0295
|View full text |Cite
|
Sign up to set email alerts
|

The Influence A Crucible Arrangement On The Electrical Efficiency Of The Cold Crucible Induction Furnace

Abstract: A big interest in application of cold crucible furnace (CCF) for industrial, particularly metallurgical, processes has been observed in recent years. They are mainly utilised for melting of metal, glass and other materials. Analyses of processes that occur in such devices are performed; however, computer modelling is rarely applied. As a precise determination of the electromagnetic field distribution is essential for a proper analysis of processes in furnaces with cold crucibles, a complex 3D model development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The authors of [7] reported that the number of the crucible segments, as well as the width of the slits between the segments, affects the electromagnetic field significantly and, in consequence, the crucible performance. Similar analysis was presented in [8]. The authors of that work investigated the crucible wall arrangements on the efficiency of the melting in CCF.…”
Section: Introductionmentioning
confidence: 60%
“…The authors of [7] reported that the number of the crucible segments, as well as the width of the slits between the segments, affects the electromagnetic field significantly and, in consequence, the crucible performance. Similar analysis was presented in [8]. The authors of that work investigated the crucible wall arrangements on the efficiency of the melting in CCF.…”
Section: Introductionmentioning
confidence: 60%
“…The frequency was a constant parameter due to the design of the furnaces and their optimal use. This frequency was respectively 3.5 kHz for ICF and 8 kHz CCF [17,18].…”
Section: Methodsmentioning
confidence: 97%
“…Each time, the water in the washer was replaced to provide comparable conditions of the mixing process (temperature) – the physical and chemical processes in the volume depend on the temperature as well as other environment conditions. 21 A part of selected types of samples did not undergo ultrasonic mixing (see Table 1) for the evaluation of the effect of this process on some of the examined properties.…”
Section: Methodsmentioning
confidence: 99%